Algunas falacias respecto a las políticas de autoconstrucción en los países en desarrollo - Burgess, Rod (El Colegio de México A.C., 1988)
In recent years the main international financial organizations have given preference to those projects concerning sites and services, the improvement of hovels, and irregular squatting; the objective of this article is to analyse the experience gained from these projects and the theoretical discussions on housing self-construction stemming from this. It aims at demonstrating that these policies lead to myths and fallacies which tend to hide the true nature of the problems arising from the projects. Mentioned as examples of these fallacies are: that the interest of the international organizations in the strategies of self-construction is not new: that it is not possible to claim that the policy of self-construction has determined a solution to the housing problem in the most underdeveloped countries; neither is it feasible to claim that the self-construction projects have greatly benefited the poorest groups; nor can they establish that the sites and services and improvement projects are notable for their use of family non-remunerated labor.